2008
DOI: 10.3390/ijms9081504
|View full text |Cite
|
Sign up to set email alerts
|

TFIP11, CCNL1 and EWSR1 Protein-protein Interactions, and Their Nuclear Localization

Abstract: Previous studies using the yeast two-hybrid assay (Y2H) have identified cyclin L1 (CCNL1) and Ewing sarcoma breakpoint region 1 protein (EWSR1) as being interacting partners of tuftelin-interacting protein 11 (TFIP11). All three proteins are functionally related to the spliceosome and involved in pre-mRNA splicing activities. The spliceosome is a dynamic ribonucleoprotein complex responsible for pre-mRNA splicing of intronic regions, and is composed of five small nuclear RNAs (snRNAs) and ~140 proteins. TFIP11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…AtNTR1 immunolocalisation was investigated, to test the relationship between AtNTR1 and PolII. We confirmed previous results from human cells showing that NTR1 is localised in the nucleus but excluded from the nucleolus, using a complementing genomic NTR1‐GFP line (Supplementary Fig S1I and J) and AtNTR1 antibody (Fig B) (Tannukit et al , ). In addition, it was found that AtNTR1 is only partially co‐localised with the SC35 splicing factor using dual labelling (Fig B), which is in agreement with results concerning NTR1 mouse homologue (Wen et al , ).…”
Section: Resultssupporting
confidence: 90%
“…AtNTR1 immunolocalisation was investigated, to test the relationship between AtNTR1 and PolII. We confirmed previous results from human cells showing that NTR1 is localised in the nucleus but excluded from the nucleolus, using a complementing genomic NTR1‐GFP line (Supplementary Fig S1I and J) and AtNTR1 antibody (Fig B) (Tannukit et al , ). In addition, it was found that AtNTR1 is only partially co‐localised with the SC35 splicing factor using dual labelling (Fig B), which is in agreement with results concerning NTR1 mouse homologue (Wen et al , ).…”
Section: Resultssupporting
confidence: 90%
“…To date no disease process has been identified for a mutated TFIP11 gene locus, but aberrant splicing activities are noted in many cancers [25,26], and the molecular mechanisms responsible may relate to key splicing factor activities being adversely impacted by specific mutations. Previously, we showed that TFIP11 interacts with cyclin L1 (CCNL1) and Ewing’s sarcoma protein (EWSR1), both of which have been previously associated with pre-mRNA splicing events [16]. It is intriguing that TFIP11 may participate in multiple cellular activities as diverse as pre-mRNA splicing, cell cycle activity and tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to imaging, cells were washed with phosphate buffered saline (PBS), fixed with 4% paraformaldehyde, counterstained with DAPI, mounted in VECTASHIELD medium (Vector Labs, Burlingame, CA). Direct fluorescence confocal microscopy was performed and images were captured as previously described [3,12,16]. …”
Section: Methodsmentioning
confidence: 99%
“…EWSR1 activates other transcription factors such as POU4F1 (or BRN3A, 13q13) [7], and POU5F1 (or OCT4, 6p21) genes which regulate differentiation of neuronal cells [7, 8]. EWSR1 and CCNL1 (cyclin L1) are also interacting partners of TFIP11 (tuftelin-interacting protein 11), a protein functionally related to the spliceosome and involved in pre-mRNA splicing [9]. In normal cell physiology, EWSR1 is required for cell survival in the central nervous system [4] and performs important functions in the regulation of genomic integrity and in RNA and microRNA’s maturation processes.…”
Section: Ews Protein In Normal Cell Physiologymentioning
confidence: 99%